Determinación de la prevalencia de leucemia felina en las parroquias urbanas del cantón Latacunga. - Cuchiparte Huaraca, Dámaris Elizabeth (2023)
Feline leukemia represents a problem of great importance for domestic felines due to its multiplicity of symptoms. The objective of the investigation was to determine the prevalence of Feline Leukemia in the urban parishes of Latacunga Canton using the rapid ELISA kit. Twenty cats from the urban parishes (Eloy Alfaro, Ignacio Flores, Juan Montalvo, La Matriz, and San Buenaventura) were randomly sampled. A survey was applied to obtain information on risk factors. R-Studio software evaluated the relationship between risk factors and disease prevalence. As a result, a 10% prevalence rate was obtained, with Juan Montalvo parish having the highest percentage of 4%, San Buenaventura and Eloy Alfaro with 3%, and 0% corresponding to La Matriz and Ignacio Flores. No significant differences were observed when evaluating risk factors such as breed, sex, age, and deworming, indicating no relationship with Feline Leukemia. At the same time, vaccination, health status, habitat, and reproductive status showed a direct relationship with positive disease cases. The epidemiological map allowed the location of the urban parishes where positive cases were detected.